PENERAPAN RESTORATIVE JUSTICE DALAM PERKARA PIDANA MELALUI BHAYANGKARA PEMBINA KEAMANAN DAN KETERTIBAN MASYARAKAT (BHABINKAMTIBMAS) DI KECAMATAN BUNUT KABUPATEN PELALAWAN - Sultan Kevinsyah Dian Nugraha; Davit Rahmadan; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Minor criminal acts (Tipiring) are minor or non-hazardous criminal offenses that cover minor crimes written in the second book of the Criminal Code which consist of, light animal abuse, light abuse, minor abuse, minor theft, minor embezzlement,Legal factors, namely the provisions concerning the mechanism of investigation, have actually been regulated but there is no regulatory basis governing criminal mediation, especially in light of theft so that investigators are still hesitant to submit all cases of minor theft cases handled and citizens have not fully known and understand the applicable law related to the existence of reasoning mediation as an alternative solution to minor criminal cases.Keywords: Penerapan, Restorative Justice ,Perkara Pidana, Bhabinkamtibmas